The Law and School Students’ Socialization - Jonynienė, Živilė (Acta Paedagogica Vilnensia, 2000)
The article discusses the conception and factors of child socialization in a democratic society. Official ideology of a child, advocated by various legal documents, in the United Nations Convention on the Rights of the child in particular (1989), concedes for a child universal human rights to justice, equality, freedom, self-determination and participation. Negation of those rights for creates conditions for child’s asocialization. The discrepancy between rights advocated and rights realized advances asocialization and children delinquency. The data on extreme cases of children asocialization, delinquency, truancy and suicides in Lithuania have been presented. Tendencies of undesirable phenomena in Lithuania and other Western countries have been compared. Delinquency prevention and successful children socialization are related to adequate implementation of children rights. This is the concern of various international organizations: UN, Council of Europe, Save the children, Childwatch International.